Transposition of the great arteries: logical anatomical arterial correction. Issue 6018 (8th May 1976) - Ross, D; Rickards, A; Somerville, J
Abstract : In a 20-month-old child with classic transposition of the great arteries the pulmonary artery, coronary arteries, and aorta were successfully retransposed at arterial level. It was difficult to reimplant the coronary arteries in the dilated pulmonary artery root without damaging the attachments of the valve cusps, and it may be better to divide the pulmonary artery first to avoid this hazard. Retransposition at arterial level will not be suitable for all patients with transposition of the great arteries, and many questions about long-term outcome remain to be answered.